2021
DOI: 10.1038/s41467-020-20585-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of daytime napping and effects on cardiometabolic health

Abstract: Daytime napping is a common, heritable behavior, but its genetic basis and causal relationship with cardiometabolic health remain unclear. Here, we perform a genome-wide association study of self-reported daytime napping in the UK Biobank (n = 452,633) and identify 123 loci of which 61 replicate in the 23andMe research cohort (n = 541,333). Findings include missense variants in established drug targets for sleep disorders (HCRTR1, HCRTR2), genes with roles in arousal (TRPC6, PNOC), and genes suggesting an obes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 180 publications
(107 citation statements)
references
References 112 publications
(181 reference statements)
6
100
1
Order By: Relevance
“…A study using bioinformatics and transgenic mice approaches indicated the regulatory role of MEIS1 in neuropeptide substance p expression in the amygdala, suggesting a mechanism underlying anxiety and depression [42]. Second, the RP11-6N13.1 locus has been implicated in early sleep timing [43] and how it contributes to insomnia remains to be determined. In addition to our finding of rs126580832, rs40465 near RP11-6N13.1 has been reported to be associated with broad depression [15].…”
Section: Discussionmentioning
confidence: 99%
“…A study using bioinformatics and transgenic mice approaches indicated the regulatory role of MEIS1 in neuropeptide substance p expression in the amygdala, suggesting a mechanism underlying anxiety and depression [42]. Second, the RP11-6N13.1 locus has been implicated in early sleep timing [43] and how it contributes to insomnia remains to be determined. In addition to our finding of rs126580832, rs40465 near RP11-6N13.1 has been reported to be associated with broad depression [15].…”
Section: Discussionmentioning
confidence: 99%
“…A study using bioinformatics and transgenic mice approaches indicated the regulatory role of MEIS1 in neuropeptide substance P expression in the amygdala, suggesting a mechanism underlying anxiety and depression [42]. Second, the RP11-6N13.1 locus has been implicated in early sleep timing [43] and how it contributes to insomnia remains to be determined. Besides our finding of rs126580832, rs40465 near RP11-6N13.1 has been reported to be associated with broad depression [15].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study based on UK Biobank has revealed the positive association between FADS1 with rs174561 variant in the frontal cortex and daytime napping. Moreover, two-sample Mendelian randomization analyses have confirmed that more frequent daytime napping is correlating to independent risk factors (waist circumference and blood pressure) of cardiometabolic diseases [24] . Given the fact that many downstream inflammatory mediators are generated by the D5D-catalyzed n-6 PUFAs pathway, the correlation between daytime napping and cardiometabolic risks may be explained by activation of AA/PGs-mediated inflammatory response.…”
Section: D5d Implication In Pufa Related Diseases Including Cancermentioning
confidence: 95%